Beyond the 'salary institution': on the 'society of performance' and the platformisation of the employment relationship. (1st January 2020) - Chicchi, Federico
Abstract : In this contribution the author discusses the intimate relationship between the crisis of the wage labour system of industrial capitalism and the growing diffusion of spaces of exploitation related to the explosion of digital algorithms and platforms. In other words, it is argued that capitalist transformation (in the post-Fordist sense) has had a decisive impact on the social relationship of subordination by inscribing the practices of exploitation of labour into an extended space that the traditional category of subsumption was not able to describe effectively. Even more specifically, work in contemporary society - a society where the digital paradigm takes on an unprecedented configuration through the platformisation of capital-work relationships - is forced to redefine itself as a mere performance, where performance means an activity that is basically stripped from the social protections of paid employment and is legitimised on a social level only by virtue of its immediate commercial usability. In other words, work in the society of performance is a subjective space deprived of the (formal and substantial) protective dimensions that were specified during what is sometimes referred to as the wage-earning society. At the same time, work is also a space subjected to an extraction of value according to a precise and renewed neoliberal logic that finds in the new urban fabric a place to renew its social hegemony.